The humanitarian leader in each of us : 7 choices that shape a socially responsible life - LaFasto, Frank M. J. (Sage Publications, Inc, 2012)
"Socially Responsible Leadership is a supplementary (and core) text for undergraduate and graduate courses in leadership, servant leadership, social leadership, service learning, and Social Entrepreneurship (the latter primarily as a supplement to aid in self-discovery about one's intended mission). A common complaint among faculty these days is that it is difficult to get students to read their texts. This book contains the following approaches and features to appeal to students and to support the curriculum: Thirty stories of real people: The leaders interviewed for this book are a highly diverse group. They range in age from 16 to 88 years old. Six of them are still under 30 but are leading important efforts in areas such as stopping child sexual exploitation, helping foster children, and building wells in countries where water is scarce. Both men and women, the interviewees are multicultural in origin and in focus. They come from countries as diverse as India, Canada, Sri Lanka, Taiwan, and the United States. They are of different spiritual beliefs and religious backgrounds. Their educational levels range from middle school to doctorate level, and their incomes vary widely. Some are still in school; some have careers; some are retired. All are engaged in meaningful efforts to better the human condition somewhere in the world.End-of-chapter tools for self-discovery: These tools include exercises that encourage personal reflection as well as class discussion. This approach will pair well with additional content on leadership styles, models, and theories in a mainstream course. Focus on social responsibility, finding one's passion, and seeking personal meaning from one's work: Through the examples of the people profiled in this book and our research-based discussions, the book offers valuable insights into how each of us can connect with a social issue or need that we are passionate about and translate that connection into a meaningful, self-fulfilling helping experience. The book puts particular emphasis on identifying one's own strengths and finding ways in which those strengths can be put to use in the service of others. Chapter 9, A Larger Life, explores the relationship between helping others and personal happiness. End-of-book suggestions for getting started: A back-of-the-book section offers concrete suggestions for how to begin one's own journey toward helping others. An extended example is offered for how to take the first small step and then proceed in an incremental fashion to assuming increasing ownership of a helping effort. This step-by-step process of increasing personal responsibility is illustrated by a helpful chart titled ©þThe Spectrum of Involvement.©œ A resource section offers websites of organizations featured in the book for those who might have been inspired by the stories of the interviewees"--Provided by publisher.